Pneumatology and the Christian-Buddhist dialogue : does the Spirit blow through the middle way? - Yong, Amos. (Studies in Systematic Theology, 2012)
Recent thinking in Christian theology of religions has taken a "pneumatological turn" which asks how the doctrine of the Holy Spirit can contribute to the interreligious dialogue and to the emerging discourse of comparative theology. Pneumatology and the Christian-Buddhist Dialogue. Does the Spirit Blow through the Middle Way? tests the viability of this approach as applied to the Christian-Buddhist dialogue. Various Christian and Buddhist traditions are compared and contrasted within a pneumatological framework. Is the Holy Spirit to be found along the Buddha's middle way? Some Christians say yes, while others demur. The thesis of this volume is that such a pneumatological perspective opens up possibilities for the deepening and transformation of Christian theology in the religiously plural world of the twenty-first century.